THE EXECUTION OF GROUP COUNSELING FOR ADOLESCENT GIRLS IN LOVE TO PRECLUDE SELF-HARM BEHAVIORS - Lathifatun Nahda; Abdurrahman (Pena Cendekia Insani, 2025)
Adolescence is a stage of development that is full of dynamics, both physically, emotionally, and socially. In this phase, adolescents begin to experience various significant changes, including feelings of falling in love. This feeling often brings joy, but can also cause confusion, anxiety, and emotional stress, especially for adolescent girls who tend to be more expressive in expressing emotions. In the object i am looking for 5 informants. The purpose of the research to be achieved is to help adolescent girls who are affected by self harm activities due to falling in love in the area where the author lives by conducting observations and with interviews first and group counseling and the research i use is by using descriptive qualitative methods. The results of the study showed that of the five informants, adolescent girls had carried out self harm activities due to falling in love because of their partners.